2022
DOI: 10.1186/s40854-022-00371-4
|View full text |Cite
|
Sign up to set email alerts
|

A theory of very short-time price change: security price drivers in times of high-frequency trading

Abstract: Academic research has identified several factors that affect price movements; however, the scenario changes abruptly in the case of very short time price changes (VSTPC). This topic is not specifically examined in the existing literature; nonetheless, the behavior of the market microstructure is quite different at the subsecond scale. Indeed, below a certain psychological time threshold, most factors typically influencing price changes cease to apply. This paper analyzes several parameters considered to affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…By roughly discussing 4 types of relations between the underlying factors, Direct, Indirect, Behavioral, and Indirect behavioral, the paper concluded that the combination of previous volatility, scarce liquidity, and stop-loss orders is the prerequisite to high volatility in a very short period. Whereas, the high quantity of trading, though reasonable, is not to be proven [10].…”
Section: Very-short-time-price-change Theorymentioning
confidence: 97%
“…By roughly discussing 4 types of relations between the underlying factors, Direct, Indirect, Behavioral, and Indirect behavioral, the paper concluded that the combination of previous volatility, scarce liquidity, and stop-loss orders is the prerequisite to high volatility in a very short period. Whereas, the high quantity of trading, though reasonable, is not to be proven [10].…”
Section: Very-short-time-price-change Theorymentioning
confidence: 97%
“…The volatility of a financial asset plays an important role in the calculation and hedging of financial derivatives (such as options), as well as the measurement of risk in a financial or investment portfolio. The volatility phenomenon refers to how large an asset's prices change around the average price over a given period of time-this is a statistical measure of the commodity return margin [1]. The existence of volatility is closely related to risk in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we utilize realistic constraints (budget, trading costs and long-only rule), as well as money (anti-Martingale) and risk (trailing stop) management policies to allow for valid empirical tests. Despite the significant importance of these practical constraints and policies, they are often ignored in the existing literature (see, for instance [22,23]). Hence, their inclusion in this paper would further contribute to the research in this area.…”
Section: Introductionmentioning
confidence: 99%